EMOTIONAL SHOPPING IN E-COMMERCE: HOW ARE URBAN ADOLESCENTS SPENDING DURING THE COVID-19 PANDEMIC? Belanja Emosional di E-Commerce: Bagaimana Pengeluaran Remaja Kota Selama Pandemi Covid-19? - Amanatin, Elsa Lutmilarita; Wijaya, Atika (Jurnal Ilmu Keluarga dan Konsumen, 2023)
The presence of Covid-19 has influenced various aspects of life, including buying and selling activities. This study aims to investigate the reasons for the emergence of emotional shopping behavior in e-commerce among adolescents in Tegal City during the Covid-19 pandemic. This study used a qualitative method with a case study among adolescents who use e-commerce. Data collection techniques in this study were conducted through semi-structured interviews with 7 main participants and 7 supporting participants, non-participant observation, and documentation studies. The triangulation technique method was used to obtain valid data by comparing data from observations, interviews, and documentation. The results of this study indicate that emotional shopping behavior by adolescents in Tegal City arises because of four main factors: insecurity, brand-minded lifestyle, joining the trends, and store atmosphere, which can further be seen as the embodiment of emotional shopping. Male adolescents tend the purchase goods to support their hobbies, while female adolescents to support their physical appearance. These findings can form the basis for further research in the field of consumer psychology and adolescent shopping behavior amidst the current online shopping trend, which has become increasingly dominant even after the pandemic has passed.